Cultivation of micro-algae for Production of Biodiesel: An optimized Process - Demissie, Abebe Girma; Chinthapalli, Bhaskarrao; Tenaw, Shumet; Chitra, D. S. Vijaya (Research in Biotechnology, 2016)
Microalgae are considered as one of the potential source of biodiesel for the future. The search to obtain the potential strains from the algal diversity capable of producing oil is critical for sustainable production of biodiesel. In the present study, microalgae biomass with oil/lipid accumulation capability and their morphological features was isolated from Lake Abaya and Chamo. The algal biomass was cultivated in vitro and media optimization for maximum biomass was done using different basal media, BG-11 medium, and Chu -10. In addition the various carbon sources, nitrogen sources, pH and temperature were considered in this study for optimization. Green algae Oedogonium, Chlorella and Cladophora species were observed to be dominant species and the maximum oil per dry algal biomass was found to be from Oedogonium sp. Thus from the present study for the cultivation of the selected algae, BG-11 medium supplemented with tryptone (0.2%) sucrose (2%) and pH- 6 with incubation temperature of 300C was found to be suitable.Â These results suggest that Oedogonium sp. has several desirable features that make it a potential candidate for biodiesel production.